Problems of Psychological Counseling at School (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article focuses on revealing the essence and specificity of psychological counseling, in general, and the psychological characteristics of counseling work in school, in particular. There is a specific understanding and evidence of psychological differences in counseling teachers, parents and children, as well as the principles that guide the psychologist in his work.